Drosophila retinal degeneration A gene encodes an eye-specific diacylglycerol kinase with cysteine-rich zinc-finger motifs and ankyrin repeats. - Masai, I.; Okazaki, A.; Hosoya, T.; Hotta, Y. (Proceedings of the National Academy of Sciences of the United States of America, 1993)
The Drosophila visual mutant, carrying the retinal degeneration A gene (rdgA), has photoreceptor cells that degenerate within a week after eclosion. Morphological studies suggested that this mutant harbors abnormalities in membrane turnover of the photoreceptor cells. Biochemically, the rdgA mutant lacks an eye-specific and membrane-associated diacylglycerol kinase (DGK; EC 2.7.1.107) activity in a gene-dosage-dependent manner, suggesting that rdgA gene encodes a DGK. We report the molecular cloning and characterization of a DGK gene, which maps to the rdgA locus. This gene, designated as DGK2, has a single open reading frame that encodes 1454 amino acids. Like porcine DGK, DGK2 has two cysteine-rich zinc-finger motifs as well as a DGK catalytic domain. The DGK2 protein contains four ankyrin-like repeats at the C-terminal region, suggesting that DGK2 is likely anchored to the membrane or cytoskeleton. Northern blot analysis and tissue in situ hybridization to adult sections revealed that DGK2 is expressed exclusively in the adult retina and that the amount of its mRNA is reduced in some of the rdgA mutant alleles. Furthermore, in two rdgA alleles, rdgA1 and rdgA2, nonsense and missense mutations occur within their DGK2 gene, respectively. Thus, we conclude that rdgA encodes an eye-specific DGK, the absence of which leads to rhabdomere degeneration due to defective phospholipid turnover.